Exploring the Association Between HIV Knowledge and Prevention Attitudes Among Health Science Students - Wahyuni Lukita Atmodjo; Neneng Suryadinata; Shirley Moningkey; Rohana Uly Pradita Siregar (Fakultas Kedokteran Universitas Pelita Harapan, 2025)
ound: HIV continues to be a major public health concern worldwide, and comprehensive understanding has shown that HIV knowledge enhances effective prevention behaviors and helps prevent the transmission of the disease. Previous research conducted indicated that higher levels of knowledge were associated with more positive attitudes toward HIV prevention, specifically, 58.7% demonstrated good knowledge and 70.7% engaged in preventive actions. Health science students are a key group for HIV education, as they are future healthcare providers. However, limited research has been done among health science students. Methods: A cross-sectional study was conducted with 295 health science students consisting of 193 medical and 102 non-medical students. Participants completed two questionnaires, i.e., HIV knowledge with 24 true/false items and HIV prevention attitudes with 23 items on a Likert scale. Descriptive and inferential statistics, including chi-square tests and multivariate logistic regression, were used to analyze the data. Results: Of the respondents, 43.4% demonstrated good HIV knowledge, while 56.6% had poor knowledge. Regarding prevention attitudes, 59.7% exhibited favorable attitudes, while 40.3% had unfavorable attitudes. A significant positive association was found between HIV knowledge and prevention attitudes (p < 0.001, OR: 2.525, 95% CI: 1.546–4.123). Gender differences were noted, with females displaying more favorable attitudes (p < 0.001, OR: 2.551, 95% CI: 1.487–4.379). Medical students showed less favorable attitudes toward HIV prevention compared to non-medical students (p = 0.042, OR: 1.681, 95% CI: 1.017–2.778). Conclusions: This study highlights the influence of HIV knowledge, gender, and faculty on HIV prevention attitudes among health science students, with females and non-medical students showing more engagement in prevention efforts. These findings underscore the need for comprehensive HIV education in university curricula to enhance both knowledge and preventive behaviors.